2011
DOI: 10.1589/jpts.23.177
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Wearing Shoes Generating Micro-currents on Body Composition and Blood Lipid Concentrations of Overweight Females

Abstract: Abstract.[Purpose] This double-blind study was conducted to examine the effect of electric stimulation through micro-currents on body composition and blood lipid concentrations of overweight females after walking exercise.[Subjects] Overweight females in their 20s were randomly allocated to either an experimental group or a control group. Participants in the experimental group were given shoes generating micro-currents, while the control group wore shoes which did not generate micro-currents but were identical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has been widely reported that an active lifestyle during childhood and adolescence optimizes growth and development 14 , 15 , 16 ) . The body mass index has also been found to be related to total percentage of body fat in both boys and girls which can be influenced by genetic predisposition and environmental factors 17 , 18 , 19 , 20 , 21 , 22 , 23 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that an active lifestyle during childhood and adolescence optimizes growth and development 14 , 15 , 16 ) . The body mass index has also been found to be related to total percentage of body fat in both boys and girls which can be influenced by genetic predisposition and environmental factors 17 , 18 , 19 , 20 , 21 , 22 , 23 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, TC and TG in the exercise group significantly decreased. This result suggests that regular exercise should be performed along with an appropriately controlled diet program in order to improve blood lipid levels 15 , 16 ) . Women in middle age facing menopause are encouraged to not only perform exercises, but also run with weight training to prevent sharp loss of muscle, increase of body fat mass caused by decrease of metabolism at rest and osteoporosis resulting from decline in bone density, with a view to health maintenance and obesity management.…”
Section: Discussionmentioning
confidence: 99%